Retrofitting of auxiliary components to enhance the performance of a single-cylinder, air-cooled gasoline two-stroke engine - Abdul Aziz, Azhar; A. Latiff, Z.; M. Ali, M. F.; M. Said , M. F. (Faculty of Mechanical Engineering, 2006)
A unique stepped-piston engine was developed by a group of researchers at UTM. The development work engulfs design, prototyping and testing over a predetermined period of time. The aim is to demonstrate environmental-friendly capability producing comparable output with low-fuel consumption. In its carbureted version, it incorporates a three-port transfer system and a dedicated crankcase breather. These features will enable the prototype to have high induction efficiency and to behave very much a two-stroke engine but equipped with a four-stroke crankcase lubrication system. In the final stage of development it was subjected to a series of laboratory trials for actual performance evaluations. In an effort to further enhance its technology features, the researchers have embarked on the development of an add-on auxiliary system. The system comprises of an engine control unit (ECU), a direct-injector unit, a dedicated lubricant dispenser unit and an embedded common rail fuel unit. This support system was incorporated onto the engine to demonstrate the finer points of environmental-friendly and fuel economy features. The outcome of this complete package is described in the paper, covering the methodology and the final characteristics of the mobile power plant.